2022
DOI: 10.1108/ijwhm-05-2021-0121
|View full text |Cite
|
Sign up to set email alerts
|

Art-of-living at work: interventions to reduce stress and increase well-being

Abstract: PurposeDue to the increasing burden of stress in the workplace, it is necessary to develop interventions to prevent long-term overload. The present study is based on the concept of art-of-living, which promotes a more reflective and conscious approach to life. In study 1, an online training designed to increase well-being was administered. Study 2 investigated the impact of an art-of-living training in a workplace environment.Design/methodology/approachStudy 1 employed a two-factorial design, crossing time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, Avey et al. (2010, p. 18) lament that “theoretical mechanisms of the positive antecedents to well-being have given little attention.” In line with this, Schwarz et al. (2023) further emphasize the insufficiency of solely focusing on symptoms of problems in the pursuit of well-being.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…However, Avey et al. (2010, p. 18) lament that “theoretical mechanisms of the positive antecedents to well-being have given little attention.” In line with this, Schwarz et al. (2023) further emphasize the insufficiency of solely focusing on symptoms of problems in the pursuit of well-being.…”
Section: Introductionmentioning
confidence: 73%
“…Workplace well-being has become an important research focus, particularly given its impact on overall life satisfaction due to the substantial amount of time adults spend at work (Schwarz et al. , 2023), Moreover, research has shown a direct link between employee well-being and performance at work (Aubouin-Bonnaventure et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation